Presidential debate learning as a gateway to opinion articulation, communication intentions, and information seeking. (2nd October 2021) - Jennings, Freddie J.; Bramlett, Josh C.; Kenski, Kate; Villanueva, Isabel I.
Abstract: Presidential debates are a source of political learning for those who watch them. This study examines how learning from debates cultivates intentions for political engagement by increasing individuals' opinion articulation. Using data from a study that involved participants ( N  = 543) who watched a nine-minute video from the first 2020 general election presidential debate in which the presidential candidates answered questions about the economy, we find that people who learned most from this segment had increased ability to articulate their opinions about the candidates. Opinion articulation, in turn, was associated with people's intentions to discuss the economy with others and to engage in candidate advocacy. Ultimately, these effects were associated with increased intentions to seek additional information about the economy. The direct and indirect effects of political learning are explained.